2020
DOI: 10.3390/pharmaceutics12080726
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Intracellular Delivery Potential of Novel Sustainable Poly(δ-decalactone)-Based Micelles

Abstract: Biodegradable polymers from renewable resources have attracted much attention in recent years within the biomedical field. Lately, poly(δ-decalactone) based copolymer micelles have emerged as a potential drug delivery carrier material as a sustainable alternative to fossil-based polymers. However, their intracellular drug delivery potential is not yet investigated and therefore, in this work, we report on the synthesis and cellular uptake efficiency of poly(δ-decalactone) based micelles with or without a targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…One day later, the cell media was substituted by fresh media containing AuNP (20 μg/ml), nanogel (100 μg/ml), and AuNP@Ng (120 μg/ml) and incubated at 37°C, 5% CO 2 for 24 h ( n = 3). Afterwards, cells were harvested with trypsinization, washed twice with ice cold PBS and resuspended in 250 μl of PBS, kept on ice until analysis (Bansal et al, 2020 ). Mean fluorescence intensity was recorded by using a 561 nm excitation laser and the emission was collected by using RFP 582/15 band pass filter with LSRFortessa (BD Sciences, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…One day later, the cell media was substituted by fresh media containing AuNP (20 μg/ml), nanogel (100 μg/ml), and AuNP@Ng (120 μg/ml) and incubated at 37°C, 5% CO 2 for 24 h ( n = 3). Afterwards, cells were harvested with trypsinization, washed twice with ice cold PBS and resuspended in 250 μl of PBS, kept on ice until analysis (Bansal et al, 2020 ). Mean fluorescence intensity was recorded by using a 561 nm excitation laser and the emission was collected by using RFP 582/15 band pass filter with LSRFortessa (BD Sciences, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Close to neutral surface charge was expected from PJL‐DOX micelles owing to the PEG corona where the micelles are usually sterically stabilized instead of electrostatically. [ 3,5 ] The in vitro drug release was performed via dialysis method at pH 5.0 mimicking intracellular environment in the presence of two different concentrations of commonly used reducing agent dithiothreitol (DTT). [ 21 ] A sustained release pattern was observed for DOX from PJL‐DOX micelles and as expected, a higher percentage of the drug was released in the presence of elevated DTT concentration (Figure 2F).…”
Section: Resultsmentioning
confidence: 99%
“…PDL‐based drug delivery carriers were evaluated largely for their toxicity, biodegradability, and their potential as drug delivery carriers. [ 3–6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the uptake of IONs by endocytic pathway in various cell types (Calero et al 2015;Saadat et al 2019;Zavisova et al 2018;Youhannayee et al 2018). To elucidate the endocytic pathway, we performed a cytometry analysis to evaluate the cells after treatment with the pathway inhibitors and MAGCIT-MB (0.78 µg mL −1 for 6 h) (Rodrigues et al 2020;Bansal et al 2020). The results demonstrated that all cells have a statistically significant result for the inhibitor phenylarsine oxide.…”
Section: Internalization Of Magcit-mb Evaluated By Tem and Endocytosis Studiesmentioning
confidence: 93%